ANALYSIS OF HUMAN RESOURCE QUALITY, ENVIRONMENT, AND BENEFITS ON PERFORMANCE MOTIVATION AFFECTING EMPLOYEE PERFORMANCE - Mukrodi Mukrodi; Suhaendi Suhaendi; Endang Sugiarti (International Journal Multidisciplinary Science, 2025)
This study aims to analyze the influence of human resource quality, work environment, and performance allowances on work motivation, which impacts employee performance at PT Tasindo Mandiri Indonesia. The research employs a quantitative approach with a descriptive and associative design. Data were collected through a survey using questionnaires distributed to employees, and data analysis was conducted using Smart PLS software. The results indicate that the work environment and performance allowances have a positive and significant impact on employee motivation and performance. A comfortable and harmonious work environment enhances work enthusiasm, while adequate performance allowances serve as a rewarding factor that boosts productivity. Conversely, human resource quality has a positive but insignificant influence on motivation and performance, suggesting that other factors such as managerial recognition and work-life balance play a more dominant role in determining productivity. Furthermore, high work motivation significantly contributes to performance improvement. Therefore, companies are encouraged to strengthen training programs, create a more supportive work environment, and ensure a transparent and fair compensation system to enhance employee loyalty and performance sustainability.